Five Finlands: A mixed-method climate attitude segmentation from a housing perspective - Vainikka, Joni Tuomas; Lindfors, Joonas; Laitinen, Sara-Ellen; Salmela, Eveliina; Kemppainen, Teemu; Toppinen, Anne; Bernelius, Venla (Elsevier, 2026)
The climate changes faster than our collective sense of urgency for climate action. Previous research has acknowledged the diverse segments of climate-concerned publics but often without qualifying the discursive landscape within such groupings. In this mixed-methods-based paper, we first employ latent class analysis to random sample survey data representing the Finnish public to form a five-part classification. Second, we complement the segmentation with qualitative insights from online discussions and interview material. We name the segments Engaged, Aware, Cautious, Unsure, and Divergent based on their attitudes toward the changing climate and their housing behaviours. We also reflect on why the respondents tend to cluster into such segments based on socioeconomic, geographical, and ideological factors. Using this classification as a lens allows us to identify residents between more active or vocal opposites and sheds light on the overlooked mass that holds a key for more effective climate policies. While such a classification scheme can overlap at points and be contextual and shifting, it helps to place various approaches and attitudes to scale. By operationalising the created typology, we discuss why it is crucial to understand the views of the mass in the middle, i.e., individuals who recognise climate change but, to an extent, feel disempowered from climate-wise practices, why proliferating a societal change through these individuals has the best potential for successful climate mitigation and why it is necessary to understand their political agency for (in)action.
Keywords: Climate attitudes; Housing; Decarbonisation; Segmentation; Finland; Mixed methods; fi=Viestintätieteet|en=Communication Studies|